2008
DOI: 10.1038/nmeth.1224
|View full text |Cite
|
Sign up to set email alerts
|

Isoform discovery by targeted cloning, 'deep-well' pooling and parallel sequencing

Abstract: Describing the "ORFeome" of an organism, including all major isoforms, is essential for a systems understanding of any species; however, conventional cloning and sequencing approaches are prohibitively costly and labor-intensive. We describe a potentially genome-wide methodology for efficiently capturing novel coding isoforms using RT-PCR recombinational cloning, "deep well" pooling, and a "next generation" sequencing platform. This ORFeome discovery pipeline will be applicable to any eukaryotic species with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Full-length cDNA sequences have complete sequences of transcripts including coding regions (CDSs) or all exons and untranslated regions (UTRs), and thus facilitate subsequent studies on genomic structure and functional analysis [25].It is a time consuming and laborious process using the traditional Sanger sequencing method to obtain large collections of full-length cDNAs. Fortunately, the NGS method used in this study and other studies has shown to be an efficient approach to obtain a large number of full-length cDNAs [26][27]. In addition, over 7 000 unigenes with 5′ or 3′ UTR are also useful for obtaining full-length cDNA sequences via the primer walking method.…”
Section: Resultsmentioning
confidence: 86%
“…Full-length cDNA sequences have complete sequences of transcripts including coding regions (CDSs) or all exons and untranslated regions (UTRs), and thus facilitate subsequent studies on genomic structure and functional analysis [25].It is a time consuming and laborious process using the traditional Sanger sequencing method to obtain large collections of full-length cDNAs. Fortunately, the NGS method used in this study and other studies has shown to be an efficient approach to obtain a large number of full-length cDNAs [26][27]. In addition, over 7 000 unigenes with 5′ or 3′ UTR are also useful for obtaining full-length cDNA sequences via the primer walking method.…”
Section: Resultsmentioning
confidence: 86%
“…First, full-length ORFs corresponding to known and novel isoforms are amplified by reverse transcription followed by PCR (RT-PCR) using gene-specific primers. Pools of resulting RT-PCR products are Gateway-cloned (Walhout et al, 2000) and individual ORFs are sequenced using an NGS-based deep-well approach (Salehi-Ashtiani et al, 2008). Second, Gateway-cloned full-length isoform ORFs are transferred into various expression vectors to allow systematic functional analyses such as binary protein-protein and protein-DNA interaction assays or measurement of enzymatic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies (3)(4)(5)(6)(7) have shown that, by sequencing the mRNA content of cells, one can quantify the expression levels of known genes (by counting how often sequences from a given gene are observed) and refine their boundaries. For example, Nagalakshmi et al (3) studied the Saccharomyces cerevisiae transcriptome by mapping reads to the location of known genes to quantify expression, and to known splice sites to measure their occurrence.…”
mentioning
confidence: 99%